2007
DOI: 10.1002/jbm.b.30861
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteolytic potential of monocytes/macrophages derived from bone marrow after particle stimulation

Abstract: Harvested bone marrow cells expressed monocyte/macrophage phenotype, but not osteoclastic markers. The capacity of these cathepsin-K-positive phagocytic cells to resorb dentine discs and carbonated calcium phosphate in vitro suggests a direct role of monocytes/macrophages in bone resorption and periprosthetic osteolysis. The finding supports our hypothesis and previous histomorphometric observations on the presence of such osteolytic macrophages in vivo around loosening prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 67 publications
1
38
0
2
Order By: Relevance
“…This probably reflects interactions between multiple types of cells. Specifically, cathepsin K is expressed in monocytes and macrophages as well as in osteoclasts [52], and in human osteoblasts [53,54]. We assayed cathepsin K mRNA and did immune labeling in human CD14-positive cells and osteoblasts and results (not shown) were in accord with these reports.…”
Section: Discussionmentioning
confidence: 58%
“…This probably reflects interactions between multiple types of cells. Specifically, cathepsin K is expressed in monocytes and macrophages as well as in osteoclasts [52], and in human osteoblasts [53,54]. We assayed cathepsin K mRNA and did immune labeling in human CD14-positive cells and osteoblasts and results (not shown) were in accord with these reports.…”
Section: Discussionmentioning
confidence: 58%
“…However, monocytes that were differentiated on HDI or MDI had a significantly lower expression of CD68 that did not increase during differentiation (Fig. Recently, adherent MDM derived from bone marrow, although able to resorb dentine disks, did not express osteoclastic markers and were CD68 positive (Tamaki et al, 2007). Monocytes typically display the differentiation marker CD14 and as these cells mature into macrophages, the expression of CD14 has been shown to decrease (Ziegler-Heitbrock and Ulevitch, 1993;Kruger et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…A wealth of preclinical and clinical data showed that wear particle‐activated macrophages play an essential role in the pathogenesis of bone loss by producing multiple pro‐inflammatory cytokines and chemokines . Furthermore, macrophages may resorb bone directly by themselves or differentiate into osteoclasts . It was observed that significantly more macrophages infiltrated into the peri‐implant soft tissue with obvious crestal bone loss in the Ti + PBS group compared with Control group, whereas macrophage depletion by clodronate liposome treatment significantly attenuated the severity of Ti particles‐induced inflammation and bone resorption.…”
Section: Discussionmentioning
confidence: 99%